Changing Entrepreneurial Leadership Knowledge Competency in Higher Education: A Way to Move Forward - Ab Rahman, Anis Amira; Aziz, Mohd Ikhwan; Uthamaputhran, Satishwaran A/L; Mohamad Anuar, Nur Izzati; Md. Isa@Yusuff, Yusrinadini Zahirah; Nik Muhammad, Nik Maheran (International Journal of Criminology and Sociology, 2022)
University Leaders should have the entrepreneurial capacity to strengthen the Malaysia higher education sector. The role of higher education in economically improving Malaysia is undeniable. One of the functions of higher education is to build graduate entrepreneurs capable of creating jobs. Therefore, those talents should be led by leaders who have an entrepreneurial mindset. Unfortunately, less effective informal entrepreneurship education that relates to entrepreneurial leadership has been executed to inculcate the knowledge and skills of entrepreneurial leadership. Hence previous research that indicated the effective entrepreneurial leadership training which regards to entrepreneurship body of knowledge is scarce. Therefore, this study will also disclose the findings that relate to effective entrepreneurial leadership training that can change the knowledge of university leaders and fill in the gaps in the entrepreneurship body of knowledge. This study employs a Quantitative method that utilizes the Kirkpatrick Training Effectiveness Analysis Model. The descriptive and mean score analysis is used to indicate the changes in entrepreneurial leadership knowledge. It is found that the awareness of entrepreneurial leadership has increased, and they believe that entrepreneurship skills and behaviors can be carried out accordingly. Future research should enhance this study by utilizing Kirkpatrick Training Effectiveness Analysis Level Three.